Phytochemical Examination of Emilia sonchifolia DC. - Yadava, R.N.; Raj, Mamta (Asian Journal of Chemistry, 2010)
Three flavones i.e., luteolin m.p. 325-326 ºC, m.f. C15H10O6, [M]+ 286, quercetin m.p. 311-300 ºC, m.f. C15H10O7, [M]+ 302 and isorhamnetin m.p. 305-306 ºC, m.f. C16H12O7, [M]+ 316 have been isolated from seeds of Emilia sonchifolia DC. by various chemical gradations, colour reactions and spectral analysis.